Timing of young radio pulsars – II. Braking indices and their interpretation. Issue 2 (9th April 2020) - Parthasarathy, A; Johnston, S; Shannon, R M; Lentati, L; Bailes, M; Dai, S; Kerr, M; Manchester, R N; Osłowski, S; Sobey, C; van Straten, W; Weltevrede, P
ABSTRACT: In Paper I of this series, we detected a significant value of the braking index ( n ) for 19 young, high-$\dot{E}$ radio pulsars using ∼10 yr of timing observations from the 64-m Parkes radio telescope. Here, we investigate this result in more detail using a Bayesian pulsar timing framework to model timing noise and to perform selection to distinguish between models containing exponential glitch recovery and braking index signatures. We show that consistent values of n are maintained with the addition of substantial archival data, even in the presence of glitches. We provide strong arguments that our measurements are unlikely due to exponential recovery signals from unseen glitches even though glitches play a key role in the evolution of a pulsar's spin frequency. We conclude that, at least over decadal time-scales, the value of n can be significantly larger than the canonical 3 and discuss the implications for the evolution of pulsars.